Peningkatan Efisiensi Sel Surya Perovskite melalui Optimasi Rasio Komposisi rGO dan Polimer Co-Additive - Rahma Yuniza Putri; Rahmat Hidayat; Yahdi Bin Rus; Maria Ulfa (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2026)
This research investigates the optimization of perovskite solar cells (PSCs) based on  by engineering the active layer interface using a binary composite of Reduced Graphene Oxide (rGO) and Polyethylene Glycol (PEG) polymer co-additive. The background of this study addresses the low long-term stability and high charge recombination challenges in PSCs despite their high potential as a next-generation photovoltaic technology. The fabrication method involved sequential solution deposition steps on Fluorine-doped Tin Oxide (FTO) substrates, with rGO:PEG weight ratios varied at 2:1, 1:1, and 1:2. Photovoltaic testing under a sun simulator revealed that interface modification significantly boosts efficiency compared to the pristine control device. The experimental findings demonstrate that the balanced ratio of rGO:PEG (1:1) achieves the peak Power Conversion Efficiency (PCE) of 5.43%, driven by a massive surge in short-circuit current density () to 9.78 . This study implies that precision stoichiometric control of rGO-polymer co-additives provides a powerful synergistic strategy to enhance charge extraction and maximize the performance of inorganic perovskite solar cells.